How do you change y - -1/4 = -3(x + 1/4) into slope intercept form?

Jul 19, 2018

$y = - 3 x - 1$

Explanation:

This is slope-intercept form: $y - - \frac{1}{4} = - 3 \left(x + \frac{1}{4}\right)$

First, simplify:
$y + \frac{1}{4} = - 3 x - \frac{3}{4}$

Now subtract $\textcolor{b l u e}{\frac{1}{4}}$ from both sides of the equation:
$y + \frac{1}{4} \quad \textcolor{b l u e}{- \quad \frac{1}{4}} = - 3 x - \frac{3}{4} \quad \textcolor{b l u e}{- \quad \frac{1}{4}}$

$y = - 3 x - 1$

This now matches slope-intercept form, $y = m x + b$ where $m = - 3$ and $b = - 1$.

Hope this helps!

Jul 19, 2018

$y = - 3 x - 1$

Explanation:

$\text{the equation of a line in "color(blue)"slope-intercept form}$ is.

•color(white)(x)y=mx+b

$\text{where m is the slope and b the y-intercept}$

$\text{distribute and rearrange}$

$y + \frac{1}{4} = - 3 x - \frac{3}{4}$

$\text{subtract "1/4" from both sides}$

$y = - 3 x - \frac{3}{4} - \frac{1}{4}$

$y = - 3 x - 1 \leftarrow \textcolor{red}{\text{in slope-intercept form}}$

Jul 19, 2018

$y = - 3 x - 1$

Explanation:

Recall that slope intercept form is given by

$y = m x + b$, with slope $m$ and a $y$-intercept of $b$.

We can start by distributing the $- 3$ on the right to get

$y + \frac{1}{4} = - 3 x - \frac{3}{4}$

Next, let's subtract $\frac{1}{4}$ from both sides to get

$y = - 3 x - 1$

This equation is now in slope-intercept form.

Hope this helps!